Uma arquitetura para integração de ambientes data warehouse, espacial e agricultura de precisão - Petroski, Luiz Pedro (2017)
The aim of this work is to present a proposal of integration between Precision Agriculture, DataWarehouse / OLAP and GIS. The integration should use extensible and open components, agricultural modeling for decision support, geographical data support, communication interface between components, extension of existing GIS and Data Warehouse solutions. As a result of the integration, an open and extensible architecture was defined, with a spatial agricultural data warehouse modeling. In this way the technologies and tools are open and allow the implementation and extension of its functionalities to adapt to the agricultural scenario of decision. In order to perform the integration, the data were obtained from a farm in the city of Piraí do Sul/PR, which uses proprietary software for data management. Data was exported to the SHAPEFILE format, and through the process performed by the ETL tool, was extracted, transformed and loaded into the analytical database. Also as a source of political boundaries data of rural regions of Brazil, data from the IBGE were used. The database was modeled and implemented by PostgreSQL DBMS with the extension PostiGIS to support spatial data. To provide the OLAP query service, was used the Geomondrian server. The application was extended from the Geonode project, where it was implemented Analytic functionalities, and the interface between the application and the OLAP was performed by the Mandoline API and the OLAP4J library. And finally the interface was implemented through javascript libraries for creating charts, tables and maps. As principal result, an architecture was obtained for Data Warehouse integration, OLAP operations, agricultural and spatial data, as well as ETL process definition and the user interface.